2022
DOI: 10.3389/fgene.2022.775246
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3, FURIN, ACE1, and TNF-α Genetic Association With COVID-19 Outcomes: Systematic Review and Meta-Analysis

Abstract: Human polymorphisms may contribute to SARS-CoV-2 infection susceptibility and COVID-19 outcomes (asymptomatic presentation, severe COVID-19, death). We aimed to evaluate the association of IFITM3, FURIN, ACE1, and TNF-α genetic variants with both phenotypes using meta-analysis. The bibliographic search was conducted on the PubMed and Scielo databases covering reports published until February 8, 2022. Two independent researchers examined the study quality using the Q-Genie tool. Using the Mantel–Haenszel weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…We also found the polymorphisms ACE2 rs2285666, ACE2 rs2106809, ACE2 rs2074192, AGTR1 rs5186, and TNFA rs1800629 to be associated with increased risk of developing severe disease manifestations. Recent genome-wide association studies (GWASs) identified association of ACE2 , TMPRSS2 , CCR5 , and APOE variants with susceptibility to SARS-CoV-2 infection ( de Araújo et al, 2022 , Karlsen, 2022 Apr , Baranova et al, 2021 ). However, the studies did not find association with ACE1 , IFITM3 , AGTR1 , and TNFA .…”
Section: Discussionmentioning
confidence: 99%
“…We also found the polymorphisms ACE2 rs2285666, ACE2 rs2106809, ACE2 rs2074192, AGTR1 rs5186, and TNFA rs1800629 to be associated with increased risk of developing severe disease manifestations. Recent genome-wide association studies (GWASs) identified association of ACE2 , TMPRSS2 , CCR5 , and APOE variants with susceptibility to SARS-CoV-2 infection ( de Araújo et al, 2022 , Karlsen, 2022 Apr , Baranova et al, 2021 ). However, the studies did not find association with ACE1 , IFITM3 , AGTR1 , and TNFA .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, genetic variation of a gene likely modifies the function and expression of an encoded product, which could be considered the interindividual differences in susceptibility to several infectious diseases. So far, few studies have shown the roles of angiotensin-converting enzyme 1 (ACE1), ACE2, and transmembrane protease serine 2 (TMPRSS2) gene variants in the COVID-19 severity ( Gorbalenya et al, 2020 ; Hou et al, 2020 ; de Araújo et al, 2022 ; Gintoni et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for these discrepancies are unclear and similar to the ACE2 rs2285666 polymorphism require further exploration. Interestingly, a recent meta-analysis evaluating several polymorphisms related to COVID-19 outcomes found a significant association between the polymorphism ACE rs4646994 and COVID-19 severity ( 104 ). Results of individual association studies must be considered carefully and discrepancies in the findings may be the result of underpowered sample sizes, therefore replicates and more robust studies should be considered to validate these associations.…”
Section: Discussionmentioning
confidence: 99%